Commitment and conflict in unanimity bargaining - Topi Miettinen; Christoph Vanberg (University of Heidelberg, Department of Economics, 2024)
We theoretically investigate how the application of unanimity rule can lead to inefficient delay in collective decision making. We do so in the context of a distributive multilateral bargaining model featuring strategic pre-commitment. Prior to each bargaining round, players can declare a minimum share that they must receive in return for their vote. Such declarations become binding with an exogenously given probability. We characterize the set of stationary subgame perfect equilibria under all q-majority rules. Our results suggest that unanimity rule is uniquely inefficient. All other rules, including all-but-one, are fully efficient.
urn:nbn:de:bsz:16-heidok-349948
Keywords: C7; D7; 330; bargaining; commitment; conflict; delay; international negotiations; climate negotiations; legislative; multilateral; voting; majority; unanimity